2018
DOI: 10.2147/ott.s166264
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anticancer effects of low-dose curcumin with non-invasive pulsed electric field on PANC-1 cells

Abstract: BackgroundPulsed electric field (PEF) has been considered as a cell permeability enhancing agent for cancer treatment. Nevertheless, application of PEF for conventional electrochemo-therapy is usually at high intensity, and contact or even invasive electrodes are typically used, which may cause unwanted side effects. In this study, a non-invasive way of applying low intensity, non-contact PEF was adopted to study its combination effect with herb, curcumin, against pancreatic cancer cells and the mechanism invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Our findings are consistent with the previous studies in the literature reporting that curcumin triggers apoptosis in colon cancer cells by activating caspase 3 (Jaiswal et al, 2002;Rashmi et al, 2005;Su et al, 2006;Zhang et al, 2017;Jalili-Nik et al, 2018). Likewise in another study, curcumin therapy on the pancreatic cancer PANC-1 cells resulted in a twofold increase in Caspase 3 gene expression levels indicating once more that the anticancer activity of curcumin proceeds over activation of caspases (Lu et al, 2018). Curcumin is also responsible for directly inducing membrane and DNA degradation and the nuclear shrinkage of cell (Mortezaee et al, 2019).…”
Section: Apoptosis: Flow Cytometry Analysis and Caspase 3 Gene Expressupporting
confidence: 93%
“…Our findings are consistent with the previous studies in the literature reporting that curcumin triggers apoptosis in colon cancer cells by activating caspase 3 (Jaiswal et al, 2002;Rashmi et al, 2005;Su et al, 2006;Zhang et al, 2017;Jalili-Nik et al, 2018). Likewise in another study, curcumin therapy on the pancreatic cancer PANC-1 cells resulted in a twofold increase in Caspase 3 gene expression levels indicating once more that the anticancer activity of curcumin proceeds over activation of caspases (Lu et al, 2018). Curcumin is also responsible for directly inducing membrane and DNA degradation and the nuclear shrinkage of cell (Mortezaee et al, 2019).…”
Section: Apoptosis: Flow Cytometry Analysis and Caspase 3 Gene Expressupporting
confidence: 93%
“…The LIPEF device, which we had previously described [ 45 , 46 , 53 ], was used for exposure of the NSC-34 cells to various strength of electric field. The cells were placed between two copper flat and parallel electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the application of low intensity non-invasive electrical stimulation is a preferred treatment. In fact, we have previously demonstrated that the non-invasive low intensity pulsed electric field (LIPEF) could significantly enhance the anticancer ability of EGCG and curcumin via the synergistic stimulation on the mitochondrial function [ 45 , 46 ]. Given the successful application of LIPEF in cancer treatment, it is believed that multi-frequency components in the LIPEF signal may also induce bioeffects in neuron cells.…”
Section: Introductionmentioning
confidence: 99%
“…As a viable method in the application of physical stimuli, non-invasive PEF features external application of electric pulse to the desired area. In practice, the use of non-invasive PEF to enhance the activity of anticancer agent and lower the required dosage of agent is significantly effective, as proven by our recent studies on polyphenols with this approach [16,17]. It was found that exposure to non-invasive, low-intensity PEF (LIPEF) has strengthened the effect of low-dose curcumin in combating human pancreatic cancer PANC-1 cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the use of non-invasive PEF to enhance the activity of anticancer agent and lower the required dosage of agent is significantly effective, as proven by our recent studies on polyphenols with this approach [16,17]. It was found that exposure to non-invasive, low-intensity PEF (LIPEF) has strengthened the effect of low-dose curcumin in combating human pancreatic cancer PANC-1 cells [16]. Our team also observed the consistent effect of non-invasive LIPEF in significantly enhancing EGCG activity in human pancreatic cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%